Fragility analysis of steel MRFs: Effects of frequency-content components of near-fault pulse-like ground motions and setbacks. (October 2021) - Mashhadi, Sima; Homaei, Farshad; Asadi, Azita; Tajammolian, Hamed
Abstract: Near-fault (NF) pulse-like ground motions may contain long-period velocity pulses and high-frequency acceleration records, which impose significant damage on structures. This paper attempts to investigate the effects of forward directivity pulses and the high-frequency (residual) components of such records on the seismic performance of regular and setback structures. To this end, a group of ten-story steel moment-resisting frames with regular and irregular configuration were subjected to 55 NF records and their corresponding components. The records were classified into four groups to evaluate the effects of the ratio of the pulse period to the fundamental period of the structure, TP /T1, which is known to have critical effects on structural responses. Incremental dynamic analyses were carried out to develop fragility curves. The results revealed that pulse records with TP /T1 ≠ 1 can be the representatives of original NF pulse-like records to develop fragility curves for the regular structures. However, the fragility curves for setback frames should be developed under the original NF earthquake records, when TP /T1 ≤ 1. The residual part is the predominant component for the regular structure only when TP /T1 ≈ 1. However, in some setback frames, the effects of the residual part in exceeding the performance level are considerable even when TP /T1 > 1. Meanwhile, pulse records with TP /T1 ≈ 0.5 are the most damaging directivity pulses in the IO limit state of regular and setback structures, while the pulse records with TP /T1 ≈ 2 and TP /T1 ≥ 2 are the most critical pulses in the LS and CP performance levels of regular and setback frames, respectively.